2018
DOI: 10.1175/waf-d-18-0019.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Severe Weather Warnings, Storm Reports, and Storm Cell Frequency in and around Several Large Metropolitan Areas

Abstract: The spatial distribution of storm-based severe weather warnings, local storm reports, and radar-detected storm cells around six large cities in the central United States is examined from October 2007 to May 2017. The cities are Columbus, Ohio; Cincinnati, Ohio; Indianapolis, Indiana; Louisville, Kentucky; Nashville, Tennessee; and St. Louis, Missouri. In all six cities, warning counts within 20 km of the city center are found to vary by 20%–40%. In every city except St. Louis, a maximum in warnings is located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…A study on regions in the United States by Naylor and Sexton [18] concluded that the urbanisation of metropolitan areas may have changed the location of convective storm cells and precipitation fields. In the Mediterranean region, there is a significant interaction between urbanisation and convective precipitation, as most floods are caused by very heavy and local precipitation in urbanised areas [7].…”
Section: Introductionmentioning
confidence: 99%
“…A study on regions in the United States by Naylor and Sexton [18] concluded that the urbanisation of metropolitan areas may have changed the location of convective storm cells and precipitation fields. In the Mediterranean region, there is a significant interaction between urbanisation and convective precipitation, as most floods are caused by very heavy and local precipitation in urbanised areas [7].…”
Section: Introductionmentioning
confidence: 99%
“…To identify instances of strong, isolated convective activity over Louisville, we create a ''cone of influence'' relative to a particular location using a process described in Naylor and Sexton (2018). This creates fanlike areas emanating from the reference location in either direction (Fig.…”
Section: A Identification Of Urban and Rural Casesmentioning
confidence: 99%
“…Several recent studies have focused specifically on the impact urban areas may have on strong, deep convection capable of producing severe weather. Naylor and Sexton (2018) found that storm-based National Weather Service warnings and the frequency of convective cells with a reflectivity of 50 dBZ or more are maximized on the downwind side of several large cities. Reames and Stensrud (2018) performed Weather Research and Forecasting (WRF) Model simulations of a supercell and found that the strength of low-level rotation, as well as the track of the near-surface mesocyclone, can be impacted by the presence of a large city.…”
Section: Introductionmentioning
confidence: 99%
“…greenhouse gas emissions, anthropogenic heat, and urbanisation) have aroused more and more attentions (Karl & Trenberth 2003;Han et al 2014). Urban areas make the local weather and climate different from that in the surrounding suburbs (Naylor and Sexton 2018). In previous studies, the amount and frequency of precipitation tends to be higher in urban centers and downwind than in the surrounding areas (Ganeshan et al 2013;Zhang et al 2018).…”
Section: The Precipitation Extremes Over Urban Areasmentioning
confidence: 99%